Studi Perencanaan Untuk Performance Spoiler MCX-1 SP dan MCX-2 SP Pada Kendaraan Truk Dengan Metode Computational Fluid Dynamic (CFD) - Jawi, Herlambang Putra (2016)
Purpose of research thesis is to doing about models and behavior aerodynamic of simulation on truck vehicle with added as spoiler MCX-1 Sp and spoiler MCX-2 Sp utilize CFD simulation software. Besides to describe fluid flow phenomenon that happening around each truck vehicle models, so point drag coefficient of truck will be known and gotten difference result simulated of each truck vehicle models. In this simulated process will be doing with variation on shaped spoiler geometry and truck vehicle speed, speed variation is among 5 m/s until 25 m/s with speed interval 5 m/s. Models made in scale suitably being meant to describe flow behaviour at front and also behind truck and simulation vehicle is to doing on steady state condition. Result of research to point out that average of drag coefficient value is lowest happens on truck with spoiler MCX-2 Sp as big as 0,192000036 and drag coefficient value is supreme happens on truck without spoiler as big as 0,21183409. This proves that added as spoiler MCX-2 Sp on truck can reduce drag coefficient on truck than another models. Key Word : Truck, Speed, Drag Coefficient, Aerodynamic, CFD.